2021
DOI: 10.1002/cncr.33407
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome risk components and mortality after triple‐negative breast cancer diagnosis in postmenopausal women in the Women's Health Initiative

Abstract: BACKGROUND: Triple-negative breast cancer (TNBC) has a high recurrence risk and poor clinical outcomes. Associations between metabolic syndrome (MetS) risk components and mortality in postmenopausal women with TNBC were examined in the Women's Health Initiative. METHODS: Five hundred forty-four postmenopausal women were diagnosed with nonmetastatic TNBC. Baseline risk components included a high waist circumference (≥88 cm), high blood pressure, hypercholesterolemia, and diabetes. Groups were categorized by the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…Increased BMI can adversely affect response to agents such as VEGF inhibitors [146], endocrine therapy in breast cancer [144], hematologic chemotherapy toxicity in gynecologic cancer [142], and outcomes after SBRT for prostate cancer [147]. The occurrence of metabolic syndrome and poor glucose control in obese cancer patients can increase the risk of non-cancer death in survivors [151] and increase the susceptibility to infections including SARS-CoV-2 (COVID-19) [152][153][154][155]. Aerobic and resistance exercise are means to reduce sarcopenia in obese and non-obese can-cer patients [145,156].…”
Section: Discussionmentioning
confidence: 99%
“…Increased BMI can adversely affect response to agents such as VEGF inhibitors [146], endocrine therapy in breast cancer [144], hematologic chemotherapy toxicity in gynecologic cancer [142], and outcomes after SBRT for prostate cancer [147]. The occurrence of metabolic syndrome and poor glucose control in obese cancer patients can increase the risk of non-cancer death in survivors [151] and increase the susceptibility to infections including SARS-CoV-2 (COVID-19) [152][153][154][155]. Aerobic and resistance exercise are means to reduce sarcopenia in obese and non-obese can-cer patients [145,156].…”
Section: Discussionmentioning
confidence: 99%
“…An analysis of 544 women with non-metastatic TNBC showed that those with a greater number of MS components had a 27% lower 10-year BC-overall survival, non-significantly higher BC-specific mortality (HR 2.05, P trend =0.114) and significantly higher BC-overall mortality (HR 2.13, P trend =0.006), likely because of reduction in other causes of death ( 57 ); while another report showed that higher physical activity was associated with lower all-cause (HR 0.86, P trend <0.001), but not BC-specific mortality (HR 0.85, p=0.09) ( 63 ).…”
Section: B Shared Outcomes Between Cancer and Cvdmentioning
confidence: 99%